PRONOMINA PERSONA DALAM BAHASA JAWA DI PERBATASAN KABUPATEN MALANG DAN KABUPATEN BLITAR - Ana Mardiana, Dwi Ira Ningrum (University of Brawijaya, 2020)
This article aims to describe the personal pronouns in Javanese which are used by citizen in the border area of Malang and Blitar Regency. Researcher used qualitative descriptive method in this article with unstructured interviews. There are 3 (three) informants in each research point (TP), so, there are 18 (eighteen) informants in this article. The results of this article is that there are various types of personal pronouns in Javanese. The word awakdewe for first personal pronouns is equivalent with kita in Bahasa Indonesia. The words awakmu, koen, kowe, dan sampean are second personal pronouns which is equivalent with word kamu in Bahasa Indonesia. The words dekne, dek e, and bocahe as the third personal pronouns are equivalent with the word dia. The use of personal pronouns for the citizen in the border area is also influenced by the distribution of cultural areas (tlatah) in East Java.